Indicators of Authentic Leadership among Secondary School Principals in East Jerusalem: A Perspective from School Teachers - Shqairat, Tahani Khalil; Shqairat, Abeer Adnan; Jondi, Nabil Jebreen (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed to identify the indicators of authentic leadership practised by secondary school principals in East Jerusalem from the perspectives of teachers. Methods: The study employed a mixed research method, combining qualitative and quantitative approaches. The authentic leadership scale, comprising four dimensions: Self-Awareness, Internalized Moral Perspective, Relational Transparency, and Balanced Processing, was administered to a random sample of 228 teachers from 10 secondary schools in East Jerusalem. Additionally, qualitative interviews were conducted with seven school teachers, and the grounded theory approach was used to analyze the collected data. Results: The study revealed high indicators of authentic leadership among school principals across the dimensions of Internalized Moral Perspective, Balanced Processing, Self-Awareness, and Relational Transparency. The quantitative and qualitative findings were congruent and discussed in detail. Conclusions: The study highlights the importance of enhancing authentic leadership in secondary schools by fostering the capacity of school principals in authentic leadership practices.